Kaingin II, Pansol: Cultural and psychological adaptation of rural migrants in an urbanizing barrio - Lagmay, Leticia A. (Philippine Social Sciences Review; Understanding Filipino Migration, Eds., Aurora E. Perez and Maruja Milagros B. Asis, 2011)
None
Keywords: rural migrants, migration